Virtual reality and news audiences: empathy or more? - Rodenbaugh, Mikaela, author; Humphrey, Michael, advisor; Long, Marilee, committee member; Parks, Elizabeth, committee member (Colorado State University. Libraries, 2020)
In this master's thesis, I analyzed the following question: "Does VR journalism increase empathy or prosocial behavior in news audiences?" In doing so, I also balanced considerations of other modifiers of prosocial behavior. Multiple pre-test orientations were measured via the Toronto Empathy Questionnaire, the Five Factor Model of Personality, and the Ideological Consistency Scale. Then, participants were asked to watch or read The New York Times documentary "The Displaced" in three randomly assigned conditions: via a head-mounted display (HMD) Oculus Go device, using a computer mouse to click around in the YouTube 360- degree video, and via print from The New York Times Magazine. After watching or reading "The Displaced," participants were given the SUS Presence Questionnaire which measures immersion as well as the helping behaviors scale. Results showed no strong relationship between VR journalism and empathy or helping behavior in news audiences, in contrast to previous studies, however there was a strong relationship between level of immersion and story medium. There was also a strong relationship between personality disposition, empathetic capacity, and political ideology with participants' willingness to help those affected by the refugee crisis. I discuss both the ramifications of this study for newsroom practices and future research of immersive media.
Keywords: empathy; immersive journalism; virtual reality; immersion; empathetic capacity; media effects